Inside Cover: Red‐ and Far‐Red‐Emitting Zinc Probes with Minimal Phototoxicity for Multiplexed Recording of Orchestrated Insulin Secretion (Angew. Chem. Int. Ed. 49/2021). Issue 49 (4th October 2021) - Zhang, Junwei; Peng, Xiaohong; Wu, Yunxiang; Ren, Huixia; Sun, Jingfu; Tong, Shiyan; Liu, Tianyan; Zhao, Yiwen; Wang, Shusen; Tang, Chao; Chen, Liangyi; Chen, Zhixing
Abstract : Insulin secretion from β‐cells in intact islets can now be recorded together with calcium signal and organelles. In their Research Article on page 25846, Zhixing Chen and co‐workers developed a new class of red‐ and far‐red‐emitting Zn 2+ probes with minimal phototoxicity. Tailored for 4D, long‐term, and multiple‐color recording of Zn 2+ /insulin co‐secretion in β‐cells and islets, the new probes promise to unveil the spatial‐temporal regulation of islet endocrinology.